Hemodynamic Phenotyping of Pulmonary Hypertension in Left Heart Failure. (September 2017) - Naeije, Robert; Gerges, Mario; Vachiery, Jean-Luc; Caravita, Sergio; Gerges, Christian; Lang, Irene M.
Abstract : Increased pulmonary venous pressure secondary to left heart disease is the most common cause of pulmonary hypertension (PH). The diagnosis of PH due to left heart disease relies on a clinical probability assessment followed by the invasive measurements of a mean pulmonary artery pressure (PAP) ≥25 mm Hg and mean wedged PAP (PAWP) >15 mm Hg. A combination of mean PAP and mean PAWP defines postcapillary PH. Postcapillary PH is generally associated with a diastolic pulmonary pressure gradient (diastolic PAP minus mean PAWP) <7 mm Hg, a transpulmonary pressure gradient (mean PAP minus mean PAWP) <12 mm Hg, and pulmonary vascular resistance ⩽3 Wood units (WU). This combination of criteria defines isolated postcapillary PH. Postcapillary PH with elevated vascular gradients and pulmonary vascular resistance defines combined post- and precapillary PH (Cpc-PH). Postcapillary PH is associated with a decreased survival in proportion to increased pulmonary vascular gradients, decreased pulmonary arterial compliance, and reduced right ventricular function. The Cpc-PH subcategory occurs in 12% to 13% of patients with PH due to left heart disease. Patients with Cpc-PH have severe PH, with higher diastolic pulmonary pressure gradient, transpulmonary pressure gradient, and pulmonary vascular resistance and more pronounced ventilatory responses to exercise, lower pulmonary arterial compliance, depressed right ventricular ejection fraction, and shorter life expectancy than isolated postcapillary PH. Cpc-PH bears similarities to pulmonary arterial hypertension. Whether Cpc-PH is amenable to therapies targeting the pulmonary circulation remains to be tested by properly designed randomized controlled trials.